The craft of public administration in Eurasia. (October 2020) - O'Connor, Karl; Carmichael, Paul
In an innovative approach, applied to a region of the world on which research remains in its infancy, this article identifies the dominant administrative reform traditions embedded within the administrative elites responsible for administrative reform in Eurasia. Our contribution is twofold. Firstly, we establish a mechanism for measuring bureaucrat perceptions of administrative reform that may be replicated in other regions, by identifying the extent to which the three dominant Western traditions of public service (traditional public administration, new public management and new public governance) have been embedded in Eurasian societies. The article thereby demonstrates the effectiveness of these turns in public administration to be 'learned' and become embedded within the psyche of elite-level bureaucrats in these Eurasian post-Soviet regimes. The article posits that, while members of these elites hold several common governance perceptions, understanding of administrative reform differs markedly between bureaucrats and is broadly aligned with various aspects of the three dominant turns in public administration. Therefore, it is recommended that some rebalancing needs to take place between international/regional public policy interventions and public administration interventions. While public policy interventions are of course required, the administrative foundations upon which they are built (or learned), require greater attention to the needs, skills and attitudes of practitioners.